Distribution of high sensitivity troponin taken without conventional clinical indications in critical care patients and its association with mortality. (25th November 2020) - Hinton, J; Augustine, M; Gabara, L; Mariathas, M; Allan, R; Borca, F; Nicholas, Z; Beecham, R; Kwok, S; Cook, P; Grocott, M.P.W; Mamas, M.A; et al.
Abstract: Background: High sensitivity troponin (hs-cTn) concentrations above the manufacturer's upper limit of normal (ULN) are frequently seen outside the context of MI, particularly in critical care units. The current evidence regarding the prognostic value of hs-cTn in critical care settings is discrepant. Purpose: To describe the distribution of hs-cTn in a consecutive cohort of patients in critical care units, regardless of whether there is a conventional clinical indication, and the association of this distribution with clinical outcomes. Methods: Consecutive patients admitted to three adult critical care units (cardiothoracic (CCU), general (GCU), neuroscience (NCU)) over a six month period had hs-cTnI tests performed serially throughout the admission, regardless of whether the supervising team felt there was a clinical indication. The results were nested and not revealed to patients or clinicians unless they were requested as part of routine care. The hs-cTnI results were correlated with parameters of clinical outcome. Results: After excluding those diagnosed with a type 1 MI, there were 1, 563 patients remaining in the study cohort (CCU 530, GCU 750, NCU 283). The median hs-cTnI was 77ng/L (IQR 11–1932ng/L, with 1081 (69.2%) patients above the manufacturer-provided ULN. Overall there was a bimodal distribution; GCU and NCU were positively skewed and CCU negatively skewed. Hs-cTnI concentrations above the ULN were associated with age, comorbidity, illness severity and need for organ support (table 1). The degree by which the hs-cTnI concentration was above the ULN remained an independent predictor of critical care mortality (figure 1) in NCU and GCU. Conclusion: Hs-cTnI elevation taken outside the context of conventional clinical indications is common in the critically ill and is associated with age, comorbidity and illness severity. Admission hs-cTnI is an independent predictor of mortality and provides additional discriminative ability to the APACHE II score alone. This assay may represent a novel prognostic biomarker on admission in non-CCU critical care settings. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Beckman Coulter